(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
The notion of anthropo-poiesis developed in the anthropological field includes all those practices put in place by each human group and tending to “build” the human being, understood as an “incomplete” animal and therefore needing a cultural completion. The notion can also be extended to the study of the hero: a heroo-poietic perspective can be oriented towards 1) the poiesis of the hero in the phase of his initiation, 2) the heroic semiology in any specific textual or cultural context, 3) the overall role played by the hero in a culture, 4) the ways in which a hero can become an instrument for cultural construction and therefore for the making of the human being (anthropology of the hero).